"A \\text{ is an event}, p=P(A).\\\\\n\\text{Trials are conducted until }A\\text{ occurs}.\\\\\nP\\{X=k\\}=(1-p)^{k-1}p, k=1,2,\\ldots\\\\\nP\\{X>i+j|X>i\\}=\\frac{P\\{X>i+j,X>i\\}}{P\\{X>i\\}}=\\frac{P\\{X>i+j\\}}{P\\{X>i\\}}=\\\\\n=\\frac{\\sum_{k=i+j}^\\infty (1-p)^kp}{\\sum_{k=i}^\\infty (1-p)^kp}=\\frac{\\frac{(1-p)^{i+j}p}{1-(1-p)}}{\\frac{(1-p)^{i}p}{1-(1-p)}}=\\frac{(1-p)^{i+j}}{(1-p)^i}=(1-p)^j.\\\\\n\\text{Here first we used the formula of conditional probability}\\\\\n\\text{and then the formula of sum of geometric progression}.\\\\\nP\\{X>j\\}=\\sum_{k=j}^{\\infty} (1-p)^k p=\\frac{(1-p)^jp}{1-(1-p)}=(1-p)^j\\\\\n\\text{(we used the formula of sum of geometric progression)}."
Comments
Leave a comment